Fishermen Intentions Toward Floating Net Cage based on Technology Acceptance Model and Theory of Reasoned Action - Suef, Mokh; Kurniati, Nani; Azizah, Farras Rahardini (Institut Teknologi Sepuluh Nopember, 2019)
In order to support offshore aquaculture in Indonesia, a floating net cage is being developed by Pusat Studi Kelautan ITS and will be placed in Sidoasri Village, Malang, Indonesia. The use of floating net cage will shift the habits of the fishermen. It will be very for the effort of developing the floating net cage if it will be rejected by the fishermen. Therefore, it is important to measure the factors influencing fishermen intention as a potential user to use the cage. In this paper, Technology Acceptance Model is integrated with Theory of Reasoned Action to identify the factors. The findings of this study, obtained that fishermen intentions to use floating net cage is influenced by their attitude and subjective norm, while perceived usefulness and perceived ease of use have a role to affect the intentions indirectly